Key factors influencing educational technology adoption in higher education: A systematic review. - Jiyuan Feng; Bin Yu; Wee Hoe Tan; Zetian Dai; Zengkun Li (PLOS Digital Health)
In the current globalised educational environment, higher education increasingly relied on educational technology to enhance teaching and learning outcomes. Therefore, exploring the decisive factors influencing the adoption of educational technology was crucial for its successful implementation. This paper employed a systematic review using the PRISMA method to investigate four key dimensions affecting educational technology adoption: Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions. Through a thorough examination of relevant literature, this review deepened the understanding of the core factors influencing the adoption process. A total of 1,891 studies related to educational technology adoption, published between 2015 and 2024, were initially identified, with 39 studies remaining after careful selection for analysis. The classification analysis revealed that all articles were categorised under the four themes: Performance Expectancy (8 articles), Effort Expectancy (18 articles), Social Influence (5 articles), and Facilitating Conditions (8 articles). This review provided valuable insights for higher education institutions aiming to enhance educational quality through the adoption of advanced educational technologies, and it also made a significant contribution to the existing academic literature. However, the interactions between the four dimensions warrant further exploration.